2010
DOI: 10.1586/eci.10.42
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine regulation of intestinal epithelial cell proliferation

Abstract: Evaluation of: Nava P, Koch S, Laukoetter MG et al. Interferon-g regulates intestinal epithelial homeostasis through converging b-catenin signaling pathways. Immunity 32(3), 392-402 (2010).Inflammation in the gut is associated with changes in the epithelial layer. Barrier function is diminished, epithelial cell death may occur and the epithelial cells themselves secrete proinflammatory cytokines. One of the most obvious changes, however, is in the rate of epithelial renewal, which most often manifests as incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…We observed that in contrast to the transient activation of DC, maintaining DC in the ON state permanently, which could be biologically interpreted as the constant activation of dendritic cells, created the most pro-proliferation microenvironment, in which the activation of Proliferation significantly increased and the activation of Apoptosis was blocked (line 1). This observation is supported by experimental findings that although the transient activation of DCs initiates a controlled inflammatory reaction 24 , the sustained activation of DCs leads to chronic inflammation in IBDs 25 , which enhances the growth and survival of IECs 7 26 . In addition to DC, the constant activation of MAC, CTL or TH1 in the microenvironment could also increase the activation of Proliferation while decreasing the activation of Apoptosis (lines 2, 4 and 5).…”
Section: Resultsmentioning
confidence: 53%
“…We observed that in contrast to the transient activation of DC, maintaining DC in the ON state permanently, which could be biologically interpreted as the constant activation of dendritic cells, created the most pro-proliferation microenvironment, in which the activation of Proliferation significantly increased and the activation of Apoptosis was blocked (line 1). This observation is supported by experimental findings that although the transient activation of DCs initiates a controlled inflammatory reaction 24 , the sustained activation of DCs leads to chronic inflammation in IBDs 25 , which enhances the growth and survival of IECs 7 26 . In addition to DC, the constant activation of MAC, CTL or TH1 in the microenvironment could also increase the activation of Proliferation while decreasing the activation of Apoptosis (lines 2, 4 and 5).…”
Section: Resultsmentioning
confidence: 53%